To analyze the transformation from \( f(x) = x \) to \( f(3x) - 13 = 3x - 13 \), let's break it down:
-
Starting function: \( f(x) = x \).
-
Transformation to \( f(3x) \):
- The function \( f(3x) = 3x \) involves multiplying the input \( x \) by 3. This transformation compresses the graph horizontally by a factor of 3, meaning it will appear "narrower".
-
Transformation to \( f(3x) - 13 \):
- Next, we subtract 13 from the entire function. This shifts the graph down by 13 units.
Combining these transformations, we can conclude that from \( f(x) = x \) to \( f(3x) - 13 = 3x - 13 \), the function undergoes a horizontal compression and a downward shift.
Therefore, the correct response is:
- compressed horizontally and shifted down.